2022
DOI: 10.3390/nu14173608
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Fats with All-Cause Mortality and Cardiovascular Disease Mortality among Patients with Cardiometabolic Disease

Abstract: Previous studies have shown distinct associations between specific dietary fats and mortality. However, evidence on specific dietary fats and mortality among patients with cardiometabolic disease (CMD) remains unclear. The aim of this study was to estimate the association between consumption of specific fatty acids and survival of patients with CMD and examine whether cardiometabolic biomarkers can mediate the above effects. The study included 8537 participants with CMD, from the Third National Health and Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…According to this study, there is a positive correlation between excessive protein, and cholesterol consumption and %VAT. Similar results of previous study found high consumption of cholesterol can increase abdominal VAT mass [32] that can lead to CVD mortality [33].…”
Section: Discussionsupporting
confidence: 88%
“…According to this study, there is a positive correlation between excessive protein, and cholesterol consumption and %VAT. Similar results of previous study found high consumption of cholesterol can increase abdominal VAT mass [32] that can lead to CVD mortality [33].…”
Section: Discussionsupporting
confidence: 88%
“…Dietary intake data from two days were more accurate than data from a single day. 24 Participants were asked to recall what foods and drinks they had consumed in the 24 hours preceding the interview. In this study, six dietary antioxidants were studied: vitamin A, vitamin C, vitamin E, zinc, selenium, and carotenoids.…”
Section: Methodsmentioning
confidence: 99%
“…The mean of nutrient intakes from day 1 and day 2 of the 24 h dietary recall interview were used in the analysis. Using dietary intake data from two nonconsecutive days is a more accurate estimation method than using data from a single day [ 19 ].…”
Section: Methodsmentioning
confidence: 99%